A Novel Role of Vesicles as Templates for the Oxidation and Oligomerization of p‐Aminodiphenylamine by Cytochrome c. Issue 5 (31st March 2017) - Luginbühl, Sandra; Iwasaki, Fumihiko; Chirackal Varkey, Elizabeth; Umakoshi, Hiroshi; Walde, Peter
Abstract : The oxidation and subsequent oligo‐ or polymerization of aniline or the N‐C‐ para coupled aniline dimer p ‐aminodiphenylamine ( N ‐phenyl‐1, 4‐phenylenediamine) with H2 O2 ‐dependent heme peroxidases in aqueous medium at pH = 4.3 is strongly influenced in a positive way by the presence of anionic polymers, micelles or vesicles as soft 'templates' (macromolecular or polymolecular additives), to yield products which resemble the emeraldine salt form of polyaniline (PANI‐ES). The positive effect the templates exert on the reaction mainly originates from interactions between the templates and the monomers, reaction intermediates and products, whereby the reaction occurs localized in the vicinity of the templates, suppressing undesired side reactions. As shown in the present work, the templates may even play an additional role, depending on the type of catalyst. Through interactions between the heme protein cytochrome c and anionic vesicles, cytochrome c gains increased peroxidase activity. In this way, the templates not only serve for hosting the oxidation and oligo‐ or polymerization reactions for obtaining PANI‐ES type products, but also simultaneously activate the catalyst in order to trigger the reaction. Abstract :